Business Growth in Ecuador: A Perspective from Penrose’s Theory of Resources and Capabilities - Morales-Urrutia, Ximena (2021)
In recent years, the business sector worldwide has experienced significant growth; several elements have contributed to this result, among them, resources and business and managerial capabilities stand out. Likewise, proper combination of productive resources is a precise formula that generates a competitive advantage that, in turn, makes a company unique in relation to the competition. In this context, business growth is directly related to the merger of a series of new resources, accompanied with the appropriate management of human talent. The objective of this research is focused on analysis of the factors that influence Ecuadorian business growth. To fulfill this objective, the methodology was based on the application of the two-stage cluster statistical analysis technique that groups data sets into different groups or combinations. The results suggest that the existence of different internal factors or the combination of these generates business growth.